ANALYSIS OF THE SOCIODEMOGRAPHIC PROFILE OF PEOPLE INFECTED WITH CORONAVIRUS DISEASE 19 IN THE CITY OF CAMPO MOURÃO, PARANÁ, BRAZIL (Interdisciplinary Studies Journal, 2025)
At the end of 2019, a disease caused by the new coronavirus, SARS-CoV-2, was discovered in China, which spread rapidly throughout the world, causing several impacts on society and human life in general. In late 2019, a disease caused by the novel coronavirus, SARS-CoV-2, was discovered in China and quickly spread worldwide, causing significant impacts on society and human life in general. This study investigated the sociodemographic profile of COVID-19 cases in Campo Mourão, Paraná, between March 2020 and February 2022. Using a quantitative approach and a cross-sectional epidemiological design, the research analyzed COVID-19 case notification records from the Municipal Health Department. The data were organized in an Excel spreadsheet for evaluation.Among the main findings, it was observed that females accounted for the majority of cases (53.57%), yet males had a higher mortality rate, with a 1.59 times greater likelihood of death compared to females. Healthcare and public safety professionals were the most affected occupational groups. In terms of age, the 19-35 age group had the highest infection rate, while those aged over 51 recorded the most deaths. Regarding ethnicity, most infected individuals were White (48.11%), followed by Brown (18.14%), Black (1.41%), Yellow (0.91%), and Indigenous (0.02%).The research provides a detailed view of the spread and impact of COVID-19 in Campo Mourão, highlighting relevant demographic and occupational factors. This data is valuable for guiding future public health strategies, particularly in relation to protecting vulnerable groups.18.14%, black with 1.41%, yellow with 0.91% and indigenous with 0. 02%. In general, taking into account the specificity of the research carried out in Campo Mourão, the study presents some results.
Keywords: SARS-CoV-2; Coronavirus; Surveillance; Health Vulnerability